2014
DOI: 10.1186/1756-0500-7-556
|View full text |Cite
|
Sign up to set email alerts
|

Why do women not deliver in health facilities: a qualitative study of the community perspectives in south central Ethiopia?

Abstract: BackgroundIn Ethiopia most childbirth occurs at home and is not assisted by skilled birth attendants. On the other hand having a birth attendant with midwifery skills during child birth is one of the most important interventions in reducing maternal morbidity and mortality. The objective of this study was to make an in-depth assessment of reasons why mothers do not use health facilities for child delivery.MethodsFocus Group Discussions were used to gather information on use of health facilities for delivery in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
78
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 19 publications
10
78
1
1
Order By: Relevance
“…For example, in Ethiopia, delivery at health institutions costs $17–22, while home delivery with traditional birth attendants costs only $0.8. Consequently, poor families may choose not to use SBA during deliveries [38]. Secondly, travel costs and foregone earnings are important opportunity costs in consuming health services for the poorest households, especially those living in remote rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Ethiopia, delivery at health institutions costs $17–22, while home delivery with traditional birth attendants costs only $0.8. Consequently, poor families may choose not to use SBA during deliveries [38]. Secondly, travel costs and foregone earnings are important opportunity costs in consuming health services for the poorest households, especially those living in remote rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Gitimu and colleagues [26] reported in a study in Kenya that only 40.3 % of births were attended by skilled personnel. Meselech et al found in a qualitative study in South Central Ethiopia that majority of women gave birth at home and home delivery is taken as a common practice [27]. This difference could be attributed to the differences in financial access to maternal health services.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason TBAs are encourage and are given incentives to refer all labouring women to the nearest health facility and therefore the trends of deliveries conducted by them are expected to decline [17]. Meselech et al, however concluded in their study that women relied on Traditional Birth Attendants for delivery as a result of varying reasons including cost of service [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Even though there are no costs for maternal services in public health facilities, it has been observed mothers spend money for transportation, food and purchase of drugs and supplies. These were important reasons for the low utilization of delivery services in other similar studies conducted in Ethiopia and other places as well [11,15,18,27,28]. Making sure essential supplies and drugs are available at all times and the mothers who come seeking the services return satisfied is critical to achieve higher coverage for maternity services.…”
Section: Discussionmentioning
confidence: 99%